The Effect of Culturally Familiar Text on Low-Proficiency Reader’s Reading Comprehension - Novita, Dewi; Hamied, Fuad Abdul; Sukyadi, Didi (NOBEL: Journal of Literature and Language Teaching, 2023)
The study examines the effect of culturally familiar text on the reading comprehension of low-proficiency readers in Indonesia. There were sixty-two second-year college students involved in the study as participants. The study used reading comprehension tests to gather the data. The results revealed that students with culturally familiar text had outperformed those with culturally unfamiliar text in reading comprehension. It is also found that these low-proficiency readers’ reading comprehension has improved significantly by using culturally familiar text in their reading practices. Interestingly, the students showed good engagement after being taught text that contained familiar culture. Finally, it can be concluded that the research results provide important insights, particularly for EFL educators, researchers, and learners, on the impact of culturally familiar contexts in facilitating reading comprehension achievement for low-proficiency readers in Indonesia.